Effect of heat source on ambient density in double nonlinearity heat dissipation processes in multidimensional areas: Effect of heat source on ambient density in double nonlinearity heat dissipation processes in multidimensional areas - Raufov, Rufat; Matyakubov, A.S.; Mamatov , A.U. (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
Abstract. In this research, we investigate the modeling of cross-diffusion systems that are not in equilibrium. For a particular equation, it is shown that the parameter values exist and have a numerical solution. A source describes the system of equations considered in this study as being based on the majority of physical processes, such as the cross-diffusion process in this system, thermal conductivity, and polytrophic filtration of gas and liquid in nonlinear media. Numerous partial solutions exist for these equations.